Emerging and Re-emerging Vector-Borne Infectious Diseases and the Challenges for Control: A Review - Chala, Bayissa; Hamde, Feyissa (Frontiers in Public Health, 2021)
Vector-borne emerging and re-emerging infectious diseases pose a significant public health threat worldwide. Some of these diseases are emerging and/or re-emerging at an increasing rates appearing in new regions in the past two decades. Studies emphasized that the interactions between infectious agents, hosts, and the environment are key components for the emergence or re-emergence of these diseases ecological factors. In addition, the effects of social and demographic factors including expanding human populations, urbanization, international trade and travel and intensive livestock keeping systems have significantly been associated with the emergence and/or re-emergence of vector-borne infectious diseases. Other studies emphasize the ongoing evolution of pathogens, proliferation of reservoir populations, and antimicrobial drug use to be the principal drivers for emergence and re-emergence of vector-borne infectious diseases. Still other studies equivocally claim that climate change has been linked to emergence and re-emergence of vector-borne infectious diseases. Despite many important emerging and re-emerging vector-borne infectious diseases are becoming better controlled, our success in stopping the many new emerging and re-emerging vector-borne infectious diseases that may appear in the future seems to be uncertain. Hence this paper reviews and synthesizes the existing literature to explore global patterns of emerging and re-emerging vector-borne infectious diseases and the challenges for their control. It also attempts to give insights to the epidemiological profile of major vector-borne diseases including Zika fever, dengue, West Nile fever, Crimean-Congo hemorrhagic fever, Chikungunya, Yellow fever, and Rift Valley fever.